Intestinal Lymph Flow, and Lipid and Drug Transport Scale Allometrically From Pre-clinical Species to Humans - Trevaskis, Natalie L.; Lee, Given; Escott, Alistair; Phang, Kian Liun; Hong, Jiwon; Cao, Enyuan; Katneni, Kasiram; Charman, Susan A.; Han, Sifei; Charman, William N.; Phillips, Anthony R. J.; Windsor, John A.; et al. (Frontiers in Physiology, 2020)
The intestinal lymphatic system transports fluid, immune cells, dietary lipids and highly lipophilic drugs from the intestine to the systemic circulation. These transport functions are important to health and when dysregulated contribute to pathology. This has generated significant interest in approaches to deliver drugs to the lymphatics. Most of the current understanding of intestinal lymph flow, and lymphatic lipid and drug transport rates, comes from in vitro studies and in vivo animal studies. In contrast, intestinal lymphatic transport studies in human subjects have been limited. Recently, three surgical patients had cannulation of the thoracic lymph duct for collection of lymph before and during the stepwise increase in enteral feed rate. We compared these data to studies where we previously enterally administered lipid and the lipophilic drug halofantrine to mice, rats and dogs and collected lymph and blood (plasma). The collected lymph was analysed to compare lymph flow, triglyceride (TG) and drug transport rates, and plasma was analysed for drug concentrations. Lymph flow rate, TG and drug transport increased with lipid administration in all species tested, and scaled allometrically according to the equation A = aME where A is the lymph transport parameter, M is animal body mass, a is constant and E is the allometric exponent. For lymph flow rate and TG transport, the allometric exponents were 0.84-0.94 and 0.80-0.96, respectively. Accordingly, weight normalised lymph flow and TG transport were generally lower in larger compared to smaller species. In comparison, % drug transport via lymph increased in a greater than proportional manner with species body mass with an exponent of 1.3. The supra-proportional increase in lymphatic drug transport with species body mass appeared to be due to increased partitioning of drug into lymph rather than blood following absorption. Overall, this study demonstrates that intestinal lymphatic flow, lipid and drug transport in humans is most similar to species with higher body mass such as dogs and underestimated by studies in rodents. Notably, lymph flow and lipid transport in humans can be predicted from animal data via allometric scaling, suggesting the potential for similar relationships with drug transport.